2008
DOI: 10.1084/jem.20080159
|View full text |Cite
|
Sign up to set email alerts
|

IL-12– and IL-23–modulated T cells induce distinct types of EAE based on histology, CNS chemokine profile, and response to cytokine inhibition

Abstract: Experimental autoimmune encephalomyelitis (EAE) is an infl ammatory demyelinating disease of the central nervous system (CNS) induced in laboratory animals by active immunization with myelin antigens or by the adoptive transfer of myelin-specifi c CD4 + T cells. It is widely used as an animal model of multiple sclerosis (MS) and as a prototype of organ-specifi c autoimmunity. Until recently, EAE and MS were considered Th1 diseases, mediated by IL-12p70 -polarized, IFN-␥ -producing eff ector cells. This impress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
488
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 525 publications
(513 citation statements)
references
References 30 publications
23
488
1
1
Order By: Relevance
“…Other authors have shown that distinct effector-cell populations can mediate similar clinical effects in EAE [28]. Adoptive transfer of IL-12p70-or IL-23-polarized myelin-reactive T cells into naive hosts results in paralysis that is clinically indistinguishable between the two groups; the disease induced by each of these cell lines nonetheless differs in CNS chemokine expression patterns as well as in the composition and location of infiltrating leukocyte populations within the spinal cord [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have shown that distinct effector-cell populations can mediate similar clinical effects in EAE [28]. Adoptive transfer of IL-12p70-or IL-23-polarized myelin-reactive T cells into naive hosts results in paralysis that is clinically indistinguishable between the two groups; the disease induced by each of these cell lines nonetheless differs in CNS chemokine expression patterns as well as in the composition and location of infiltrating leukocyte populations within the spinal cord [28].…”
Section: Discussionmentioning
confidence: 99%
“…Adoptive transfer of IL-12p70-or IL-23-polarized myelin-reactive T cells into naive hosts results in paralysis that is clinically indistinguishable between the two groups; the disease induced by each of these cell lines nonetheless differs in CNS chemokine expression patterns as well as in the composition and location of infiltrating leukocyte populations within the spinal cord [28]. In our system, we detected no differences in the characteristics or distribution of the cellular infiltrate in spinal cord tissue from EAE-affected CCR6 À/À and CCR6 1/1 mice, except for the CD4 1 T-cell population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Th1 cells have been described to be more susceptible to Fas-mediated apoptosis than Th2 [14][15][16][17] and Th17 cells [18][19][20]. However, Th1 cells can be long lived and drive chronic inflammation [6][7][8][9][10][11][12][13], and can persist as effector/memory cells efficiently [24][25][26]65]. Obviously, compensatory regulatory mechanisms have to exist in those cells.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from their protective role in clearing infections, Th1 cells can initiate and maintain chronic inflammatory diseases, e.g. inflammatory bowel disease [6][7][8][9], uveitis [10], EAE [11,12] and arthritis [13]. In vitro, Th1 cells are much more sensitive to Fas-mediated apoptosis than Th2 or Th17 cells [14][15][16][17][18][19][20].…”
Section: Supporting Information Available Onlinementioning
confidence: 99%